Source Sectoral Impacts on Provincial PMx2.5Concentrations based on the CAPSS 2016 using the CMAQ Model - Kang, Yoon Hee; Kim, Eunhye; You, Seunghee; Bae, Minah; Son, Kyuwon; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
Zero-Out Contributions (ZOCs; impact) of air pollutants emitted from the thirteen major source sectors in South Korea on PMx2.5were estimated with a set of the Community Multi-scale Air Quality - Brute Force Method simulations in which emissions of each source sectors were totally removed in turn during the study period of 2019. During the emission sensitivity simulations, the Clean Air Policy Support System 2016 emission inventory was processed at a horizontal grid resolution of 9 km. Among 13 source sectors, agriculture showed a high impact (5.0 μg/x3) on the nation-wide PMx2.5concentration, but NHx4x+converted from the agricultural NHx3emissions explained only 25% of the total impact. It means that about 75% of agricultural impact is mainly attributed to SOx42x-and NOx3x-converted from their precursors released from other source sectors. Except agriculture, on-road mobile showed the highest nation-wide PMx2.5impact of 1.4 μg/x3(8.0%) followed by industrial combustion (1.3 μg/x3; 7.6%), and non-road mobile (0.9 μg/x3; 5.3%). However, industrial combustion was the highest contributor in Chungnam (impact 3.0 μg/x3) while non-road mobile, on-road mobile, and manufacturing process was the predominant contributor for Busan (2.0 μg/x3), Daegu (2.1 μg/x3), and Ulsan (2.3 μg/x3), respectively. When the total impacts of precursor emissions on the nation-wide PMx2.5were compared, NOx (2.4 μg/x3) showed the highest impacts on the PMx2.5followed by Primary PMx2.5(PPMx2.5; 1.9 μg/x3), NH3 (1.5 μg/x3), and SOx2(0.6 μg/x3). However, PPMx2.5became the dominant precursor that showed the highest impact (4.6 μg/x3) to the PMx2.5in Seoul. The national emission-to-concentration conversion rate of PPMx2.5was approximately 5 and 10 times higher than that of NOxx(to NOx3x-) and SOx2(to SOx42x+), respectively. However, the emission sectoral impacts and the emission-to-concentration conversion rates changed a few times among provinces. Overall, when developing provincial air quality improvement plans, it is strongly recommended to figure out their own key source sectors and the target precursors to regulate.
Keywords: Community Multi-scale Air Quality; Emission-toconcentration conversion rate; PMx2.5; Precursor; Source Sector; Zero-Out Contribution